Possible steroidal effect of Boswellia serrata and homeostasis of Histidine – HDC- Histamine in Psoriasis - V, Aruna; Rajakumar, Sumithira; Rajagopal, Gayathri (Jour Med Resh and Health Sci, 2022)
The autoimmune trigger of Psoriasis also takes its share from certain circulating amines released predominantly by mast cell called histamine. The cost of histamine comes certainly with lowered level of the precursor amino acid Histidine which is critical for keeping the skin free of psoriatic expression. The villain who play such ploy of depleting Histidine and the accumulation of Histamine is HDC (Histidine Decarboxylase Enzyme). We have studied HDC inhibition effect of Psorolin B ointment in toto and different herbal ingredients in the formulation. Boswellia serrata exhibited high HDC inhibition effect and the subsequent tests showed that Boswellia serrata does not have any effect of either mast cell degranulation event or in neutralizing Histamine suggesting the enzyme inhibition may be steroidal in nature. The steroid like effect of the above plant has been well established. The details of HDC inhibition assay and the medical and clinical implication of the same in Psoriasis is described in the article.